Indicators of energy efficiency in buildings: Comparison with standards in force in Argentina - Salvetti, Maria Belen (2013)
In this work we make a comparative study of the energy behaviour in different building types. We analyze three cases of office buildings and three residential buildings, and compare them with a previous sample. We seek to find correlations or differences in behavior in terms of potential energy losses and gains, and UL values compared with Argentinian Standards to verify the degree of efficiency. For energy analysis we used a software which allows the analysis of thermal and energy building performance at steady state on a monthly basis. This software is called EnergoCAD and it also determines formal indicators based on IRAM standards. We conclude that the indicators used are clear to energetically “grade” buildings and to facilitate comparisons. In turn, smaller buildings are relatively less energy efficient than larger ones. At the same time it is noteworthy that the energy inefficiency has been growing rapidly over the years. Finally it is noted that none of the cases analyzed meets the National Standards.